Pilot evaluation of a novel clinical test of reaction time in National Collegiate Athletic Association Division I football players - Eckner, J. T.; Kutcher, J. S.; Richardson, J. K. (Journal of Athletic Training, 2010)
Context: Evidence suggests that concussion prolongs reaction time (RT). We have developed a simple, reliable clinical tool for measuring reaction time that may be of value in the assessment of concussion in athletes.